2017
DOI: 10.3354/ame01859
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation kinetics and inverse isotope effect of marine nitrite-oxidizing isolates

Abstract: Nitrification, the step-wise oxidation of ammonium to nitrite and nitrate, is important in the marine environment because it produces nitrate, the most abundant marine dissolved inorganic nitrogen (DIN) component and N-source for phytoplankton and microbes. This study focused on the second step of nitrification, which is carried out by a distinct group of organisms, nitrite-oxidizing bacteria (NOB). The growth of NOB is characterized by nitrite oxidation kinetics, which we investigated for 4 pure cultures of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 78 publications
3
21
0
Order By: Relevance
“…= 2.1, n = 8) and the maximum reaction rate, V max , to be 41.4 µmol NO 2 − mg protein −1 h −1 (s.d. = 9.4, n = 6), which is highly similar to the previously reported K m(app) and V max of the closely related N. watsonii (18.7 ± 2.1 µM NO 2 − and 36.8 µmol NO 2 − mg protein −1 h −1 ) [ 55 ]. The K m(app) measured for “ Ca .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…= 2.1, n = 8) and the maximum reaction rate, V max , to be 41.4 µmol NO 2 − mg protein −1 h −1 (s.d. = 9.4, n = 6), which is highly similar to the previously reported K m(app) and V max of the closely related N. watsonii (18.7 ± 2.1 µM NO 2 − and 36.8 µmol NO 2 − mg protein −1 h −1 ) [ 55 ]. The K m(app) measured for “ Ca .…”
Section: Resultssupporting
confidence: 89%
“…Nitronauta litoralis” EB; n = 8 for N. gracilis ). The other K m(app) values were retrieved from previous studies [ 54 , 55 , 81 ]. …”
Section: Resultsmentioning
confidence: 99%
“…We identified two OTUs that belonged to the genera of Nitrobacter (class: alphaproteobacteria) which linked to N-cycling. Nitrobacter is responsible for the conversion of nitrite to nitrate which is an important pathway for nitrification (Mellbye et al, 2015;Daims et al, 2016;Jacob et al, 2017). A recent metagenomic study on zooplanktonassociated bacterial communities in marine environment detected several genes (e.g., nar, nor, nos) which could be responsible for N-cycling, especially, nitrification, denitrification and dissimilatory nitrate, and nitrite reduction to ammonium (DNRA) (De Corte et al, 2018).…”
Section: Indicator Species and Their Potential Link To Nutrient Cyclingmentioning
confidence: 99%
“…These observations suggest that marine nitrite-oxidizing bacteria (NOB), among which populations of Nitrospina and Nitrospira are most ubiquitous (11)(12)(13)(14), have similarly high affinities for nitrite. However, cultured representatives of NOB mainly originate from nonoxygenated oceanic environments, and their K m values are orders of magnitude higher than those of marine AOA (10,(15)(16)(17)(18)(19)(20)(21)(22). Only one recent study showed that the half-saturation constant K s (254 ± 161 nM) for nitrite oxidation is of the same magnitude as that of marine AOA in the low-oxygen seawater of the Eastern…”
mentioning
confidence: 99%